Some ethological details on Melanthrips fuscus (Sulzer) referred to cocoon building (Thysanoptera Aeolothripidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Neanids of M. fuscus are used to build a silk cocoon at soil, inside a preliminary cell. This is made by assembling many substrate portions, each sucked by pygopodium and carefully released to increase the cell walls all around. Silk spinning is managed by pygopodium as well.Details were appreciated on a large number of neanids stored in jars, where cocoon building was supported by pieces of blotting-paper on the ground.
Keywords: preliminary cell; silk spinning; M. fuscus; Thysanoptera